The Minimal Subcortical Electronic Threshold Predicts the Motor Deficit and Survivals in Non-Awake Surgery for Gliomas Involving the Motor Pathway - Ren, Xiaohui; Yang, Xiaocui; Huang, Wei; Yang, Kaiyuan; Liu, Li; Cui, Yong; Guo, Lanjun; Qiao, Hui; Lin, Song (Frontiers in Oncology, 2022)
PURPOSE: Direct subcortical motor mapping is the golden criteria to detect and monitor the motor pathway during glioma surgery. Minimal sub-cortical monopolar threshold (MSCMT) means the minimal distance away from the motor pathway, and is critical to decide to continue or interrupt glioma resection. However, the optimal cutoff value of MSCMT for glioma resection in non-awake patients has not been reported discreetly. In this study, we try to establish the safe cutoff value of MSCMT for glioma resection and analyzed its relationship with postoperative motor deficit and long-term survivals. METHODS: We designed this prospective study with high-frequency electronic stimulus method. The cutoff MSCMT of postoperative motor deficits was statistically calculated by receiver operator characteristic (ROC) curve and its relationship with motor deficit and survivals was analyzed by logistic and Cox regression, respectively. RESULTS: The cutoff MSCMT to predict motor deficit after surgery was 3.9mA on day 1, 3.7mA on day 7, 5.2mA 3 months, and 5.2mA 6 months. MSCMT ≤3.9mA and MSCMT ≤5.2mA independently predicted post-operative motor deficits at four times after surgery (P<0.05) but had no effect on the removal degree of tumor (P>0.05). In high-grade gliomas, MSCMT ≤3.9mA independently predicted shorter progression-free (OR=3.381 [1.416-8.076], P=0.006) and overall survivals (OR=3.651 [1.336-9.977], P=0.012). Power model has the best fitness for paired mono- and bi-polar high-frequency thresholds CONCLUSIONS: This study showed strong causual-effect relation between MSCMT and postoperative motor deficit and prognoses. The cutoff MSCMT was dug out to avoid postoperative motor deficit. Further studies are needed to establish the results above. KEY WORDS: gliomas; motor pathway; high-frequency; sub-cortical stimulation; threshold; motor deficit; prognosis